Forensic assessment on landfills leachate through electrical resistivity imaging at Simpang Renggam in Johor, Malaysia - Muhammad Syamsul Imran, Zaini; M. F., Ishak; M. F., Zolkepli (IOP Publishing, 2019)
From years to years, the usage of electrical resistivity imaging (ERI) method dominated by geophysicist has increased tremendously in the application of geotechnical engineering owing to the effectiveness of the method in term of time, cost and also data coverage. The forensic assessment performed with respect to the particular reference to ERI in assessing the landfills leachate at Simpang Renggam, Malaysia. There were two lines of ERI performed at the study area using ABEM Terrameter LS 2 set of equipment based on Schlumberger protocol. Furthermore, the analysis made based on the electrical resistivity anomaly managed to detect the presence of chemical contaminants in the soil with particular reference to the chemicals resistivity values which was associated to low resistivity anomaly. Besides, the heterogeneous of the subsurface material presented in the paper by using integrated ERI analysis enabled forensic assessment of the leachate. The leachate from the landfills was believed to occur owing to the failure of the systems in accommodating and treating the waste which became worst with the present of heavy rainfall. In retrospect, the ERI result was applicable to be adopted in detecting the leachate and thus can assist the authority in taking immediate measure to prevent the frequent water disruptions at the study area.